Virus variant–specific clinical performance of SARS coronavirus two rapid antigen tests in point-of-care use, from November 2020 to January 2022. (February 2023) - Wagenhäuser, Isabell; Knies, Kerstin; Hofmann, Daniela; Rauschenberger, Vera; Eisenmann, Michael; Reusch, Julia; Gabel, Alexander; Flemming, Sven; Andres, Oliver; Petri, Nils; Topp, Max S.; Papsdorf, Michael; et al.
Abstract: Objectives: Antigen rapid diagnostic tests (RDTs) for SARS coronavirus 2 (SARS-CoV-2) are quick, widely available, and inexpensive. Consequently, RDTs have been established as an alternative and additional diagnostic strategy to quantitative reverse transcription polymerase chain reaction (RT-qPCR). However, reliable clinical and large-scale performance data specific to a SARS-CoV-2 virus variant of concern (VOC) are limited, especially for the Omicron VOC. The aim of this study was to compare RDT performance among different VOCs. Methods: This single-centre prospective performance assessment compared RDTs from three manufacturers (NADAL, Panbio, MEDsan) with RT-qPCR including deduced standardized viral load from oropharyngeal swabs for detection of SARS-CoV-2 in a clinical point-of-care setting from November 2020 to January 2022. Results: Among 35 479 RDT/RT-qPCR tandems taken from 26 940 individuals, 164 of the 426 SARS-CoV-2 positive samples tested true positive with an RDT corresponding to an RDT sensitivity of 38.50% (95% CI, 34.00–43.20%), with an overall specificity of 99.67% (95% CI, 99.60–99.72%). RDT sensitivity depended on viral load, with decreasing sensitivity accompanied by descending viral load. VOC-dependent sensitivity assessment showed a sensitivity of 42.86% (95% CI, 32.82–53.52%) for the wild-type SARS-CoV-2, 43.42% (95% CI, 32.86–54.61%) for the Alpha VOC, 37.67% (95% CI, 30.22–45.75%) for the Delta VOC, and 33.67% (95% CI, 25.09–43.49%) for the Omicron VOC. Sensitivity in samples with high viral loads of ≥10 6 SARS-CoV-2 RNA copies per mL was significantly lower in the Omicron VOC (50.00%; 95% CI, 36.12–63.88%) than in the wild-type SARS-CoV-2 (79.31%; 95% CI, 61.61–90.15%; p 0.015). Discussion: RDT sensitivity for detection of the Omicron VOC is reduced in individuals infected with a high viral load, which curtails the effectiveness of RDTs. This aspect furthert: limits the use of RDTs, although RDTs are still an irreplaceable diagnostic tool for rapid, economic point-of-care and extensive SARS-CoV-2 screening. Graphical abstract: Image 1